EFFECTS OF NATURAL ZEOLITE AND UREA ON NH3 EMISSION AND NITROGEN UPTAKE IN RICE SOILS - Kharisun .; M. Nazarudin Budiono (International Conference on Coastal and Delta Areas, 2015)
The research was aimed at investigating the effect of natural zeolite of Taskmalayan deposit and urea fertilizer on ammonia (NH3) emission, nitrogen uptake and rice yield. The researh was a pot experiment using Eutrudept soil type conducted in a green house in the Agriculture Faculty, Jenderal Soedirman University. The experiment was factorially arranged in a randomized block design. The factors were composed of three levels of natural zeolite (equivalent to 0, 1000 and 2000 kg/ha, respectively) and two types of urea fertilizers with levels equivalent to 0, 100, 200 kg N prilled urea/ha and 0, 100, 200 kg N supergranule urea/ha, respectively. Ammonia emmited was determined using Sulfuric Acid Entrapment System, whereby each experimental pot was covered with a transparent plastic chamber into which N-free air was transferred. NH3 emitted was trapped in by dilute sulfuric acid solution. The results of the experiment indicated that application of natural zeolite could reduce N volatilized by 46 %, from 78,78 to 42,11 mg N/pot. The highest N volatilized was observed at the application of prilled urea at 200 kg N/ha (197.23 mg/pot). The applications of natural zeolite did not significantly affect nitrogen uptake by rice plants.Keywords : Zeolite, ammonia emission, rice